Impact of Fiscal Decentralization on Institutional Quality: Evidence from Developing Countries - Shelleh, Zaid (Université d'Ottawa | University of Ottawa, 2017)
This paper investigates the impact of decentralization on institutional quality. Institutional quality is measured using three indicators i.e. corruption, law and order situation and democratic accountability. While fiscal decentralization is expressed in sub-national forms of revenue and expenditure decentralization. The study uses panel data of 31 developing countries covering the time period of 1984 to 2012 and estimates a fixed effect model with instrumental variable (IV). This paper finds that revenue decentralization deteriorates institutional quality while expenditure decentralization improves it. Furthermore, institutions could be improved in terms of decrease in corruption, improvement in law and order and democratic accountability if developing countries lay more emphasis on trade openness and democracy.